2017
DOI: 10.3390/su9081297
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Construction Industrial Accidents in Korea from 2011 to 2015

Abstract: Abstract:The purpose of this study is to analyze the results of construction accidents occurred from 2011 to 2015 in Korea. The annual reports from the Ministry of Employment and Labor, Korea (MOEL), and the annual reports from the Statistics Korea were used for the analysis in this study. The gender, age, company size and accident types were chosen as a category to analyze the trend of various occupational accidents. In order to analyze the characteristics of construction accidents, incidence rates (IRs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 36 publications
0
30
0
3
Order By: Relevance
“…The occupational injury rates (incident rates and mortality rates) were measured to evaluate the occupational accidents trends in the Hong Kong construction industry. This study follows the methodology of Jo et al [18] and Chaoi et al [24], where they have utilized the incidence rates (IRs) and mortality rates (MRs) to evaluate construction fatal accident trends in China, South Korea and the U.S. For this study, the incidence rate was calculated as the total number of injuries per 100 workers engaged in the construction industry. Moreover, the mortality rates were evaluated on the number of fatalities per 100,000 workers with respect to accident type through the analysis period.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The occupational injury rates (incident rates and mortality rates) were measured to evaluate the occupational accidents trends in the Hong Kong construction industry. This study follows the methodology of Jo et al [18] and Chaoi et al [24], where they have utilized the incidence rates (IRs) and mortality rates (MRs) to evaluate construction fatal accident trends in China, South Korea and the U.S. For this study, the incidence rate was calculated as the total number of injuries per 100 workers engaged in the construction industry. Moreover, the mortality rates were evaluated on the number of fatalities per 100,000 workers with respect to accident type through the analysis period.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Another study of Jackson and Loomis [17] evaluated the fatality trends in North Carolina construction industry from 1978 to 1994. A recent study of Wanjo et al [18] for the Korean construction 2 of 16 industry was conducted to evaluate occupational injuries among workers from 2011 to 2015. Results of this study indicated that the fall of a person from height was the leading cause of fatality in the Korean construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…Also, [15] and [16] used ANP and fuzzy systems for e-procurement risk factors estimation in a manufacturing company. The study of Jo et al [17] analyzed data from accidents in Korean construction sector between years 2011 and 2015, in order to provide crucial information for defining policies to reduce construction accidents. Ghodrati, Yiu, Wilkinson, and Shahbazpour [18] proposed models to predict the safety outcome in the construction industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to analyse the characteristics of construction accidents, they used incidence rates (IRs) and mortality (MRs). After their calculation they carried out T tests and ANOVA analysis to establish the relationship between IR, MR and selected categories such as gender, age of employees or company size [24]. Kang et al investigated the frequency and trend of fall-related accidents on the basis of analysis of 20,997 accidents that occurred in the construction industry in the United States in 1997-2012, registered in the Safety and Health at Work Administration (OSHA) database [25].…”
Section: Literature Reviewmentioning
confidence: 99%